APLIKASI PUPUK KNO3 DAN ZPT EKSTRAK KECAMBAH KACANG HIJAU TERHADAP PERTUMBUHAN, PENINGKATAN RASA MANIS DAN HASIL MELON (Cucumis melo L.): The Effects of KNO3 Fertilizer and Growth Regulator Of mung Bean sprout Extract on the Growth, Sweetness Increase and Yield of melon (Cucumis melo L.) - Suratmi Suratmi; Hastin Ernawati Nur Chusnul Chotimah; Abdul Syahid (AgriPeat, 2022)
This study was aimed to discover the effect of KNO3 fertilizer and growth regulators on the sweetness level of melon and to determine the best dose of KNO3 and growth regulator fertilizers that can increase the sweetness of melon. This study used a randomized block design of two factors, namely: Factor I dose of KNO3 fertilizer with 4 levels: K0 (0g/plant), K1 (6g/plant), K2 (9g/plant), and K3 (12g/plant). Factor II: concentration of mung bean sprout extract with 3 levels: C0 (0 g/l), C1 (100 g/l), C2 (200 g/l). The results showed that the KNO3 fertilizer treatment had no significant effect on all observation variables, while the treatment with mung bean sprout extract at a dose of C1 (100 g/l), showed the best treatment